Researching Parameters Selection, Testing Circuit Configuration in Lightning Impulse Test for 500kV Single Phase Power Transformer Produced in Vietnam - Nguyen, Huu Kien (Old Journal, 2017)
This article presents the result of researching in parameters selection in testing circuit configuration for the lightning impulse (LI) 1.2/50 ms power transformers which was produced in Viet Nam. This test was performed at The National Key Laboratory for High Voltage Techniques (HVLAB) - Institute of Energy, the unique laboratory in Vietnam where this test can be perform. In order to research the lightning impluse parameters and determine the endurance of high-voltage and ultra-high electrical equipment insulation in general and particularly for 500kV power transformer, it is necessary to set a simulation voltage of standard lightning impulse at 1.2/50 ms. These results will allow evaluating the quality of the insulation system in 500kV power transformer, the withstand ability of atmospheric overvoltage or operation overvoltage according to IEC60076-3,-4: 2000, TCVN6306-3: 2006; IEC60060-1: 1989, in order to obtain safety power transformer operation in gridline.